Analisis Kualitas Hidup Orang Tua yang Memiliki Anak Berkebutuhan Khusus Di SMPLB Negeri Autis Sumut - Dira Zahara Fitri; Purbatua Manurung (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2025)
The presence of children with special needs affects the quality of life of their parents, including physical, psychological, social, and economic aspects. This study aimed to analyze the experiences of parents of junior high school students categorized as intellectually disabled (tunagrahita) at SMPLB Negeri Autis Sumatera Utara regarding their quality of life. A phenomenological qualitative approach was employed to understand the subjective experiences of ten parents through observation, structured interviews, and documentation. Data were analyzed using the Miles and Huberman interactive model. The findings indicated that parents’ quality of life is influenced by physical and mental health, financial conditions, family relationships, social support, special needs services, spiritual beliefs, career, leisure time, and community involvement. Emotional support from family, professional services, and spirituality proved to be important factors in enhancing parental well-being, whereas social stigma and limited leisure time emerged as major challenges. This study provides a basis for the development of interventions and inclusive policies to support the well-being of parents of children with special needs.